THE EFFECT OF CUSTOMER EXPERIENCE, TRUST AND SATISFACTION ON CUSTOMER LOYALTY: EMPIRICAL STUDY ON BCA MOBILE BANKING USERS - Lydia Lyvia Raudhina; Suzanna Lamria Siregar (Asosiasi Dosen Muda Indonesia, 2022)
The purpose of this study is to explain and analyze the effect of Customer Experience, Customer Trust and Customer Loyalty on BCA Mobile banking customers. The research methodology used is a quantitative approach. I used Mobile Banking BCA users for the sample as many as 100 respondents. The data collection instrument used primary data obtained by using a questionnaire. The analytical data in this study are using Validity Test, Reliability Test, Normality Test, Heteroscedasticity Test, Linearity Test, Multicollinearity Test, Multiple Linear Regression Test, T Test, Coefficient of Determination Test (R2), F Test with the help of SPSS version 24. The results of this study indicated that partially and simultaneously Experience, Trust and Customers have a significant and joint effect on BCA Mobile Banking Customer Loyalty. However, Customer Experience has an influence on Customer Loyalty but they has a negative direction too, while the one with the strongest influence is a customer with a high bheta (0.675).